Elemen-elemen Arsitektur Vernakular dalam Analisa Ruang dan Bentuk pada Gereja Pohsarang - Basri, Monica (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
Church is a sacred place for Catholics. Catholic faith itself did not come from Nusantara, hence the nonNusantara shape of Catholic church architecture. This becomes the main reason of doing this research, to analyze how local value affect a religious building that has a very different character, in contexts of space and form. The research is done by comparing three variables: architecture, catholic church philosophy, and Javanese building. Pohsarang church, a Catholic church located in Kediri, East Java is chosen as the case study. By doing the research it is known that Pohsarang church is actually a vernacular architecture, because it implements elements of vernacular architecture that is represented by Javanese culture both in its space and form.Keywords: culture, church, vernacular